2007
DOI: 10.1161/atvbaha.107.151431
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment Lutein Is Antiinflammatory in Preventing Choroidal Neovascularization

Abstract: Background-Choroidal neovascularization (CNV) is a critical pathogenesis in age-related macular degeneration, the most common cause of blindness in the developed countries. The aim of the current study was to investigate the effect of lutein supplementation on the development of the murine model of laser-induced CNV together with underlying molecular mechanisms. Methods and Results-Mice were orally pretreated with lutein daily from 3 days before laser photocoagulation untill the end of the study. The index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 42 publications
4
111
0
1
Order By: Relevance
“…It has also been shown that the administration of antioxidants can prevent light-induced retinal damage in rat retinas (Organisciak et al, 1999). More recently, dietary supplementation with L in mice has been reported to suppress laser-induced CNV formation, and to inhibit the associated inflammatory and angiogenic molecules related to CNV pathogenesis (Izumi-Nagai et al, 2007). This inhibitory effect of L on inflammatory and angiogenic processes was also confirmed in vitro by the application of L to specific cell cultures including human ARPE-19 cells (Izumi-Nagai et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has also been shown that the administration of antioxidants can prevent light-induced retinal damage in rat retinas (Organisciak et al, 1999). More recently, dietary supplementation with L in mice has been reported to suppress laser-induced CNV formation, and to inhibit the associated inflammatory and angiogenic molecules related to CNV pathogenesis (Izumi-Nagai et al, 2007). This inhibitory effect of L on inflammatory and angiogenic processes was also confirmed in vitro by the application of L to specific cell cultures including human ARPE-19 cells (Izumi-Nagai et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…More recently, dietary supplementation with L in mice has been reported to suppress laser-induced CNV formation, and to inhibit the associated inflammatory and angiogenic molecules related to CNV pathogenesis (Izumi-Nagai et al, 2007). This inhibitory effect of L on inflammatory and angiogenic processes was also confirmed in vitro by the application of L to specific cell cultures including human ARPE-19 cells (Izumi-Nagai et al, 2007). Furthermore, in early 2008, Hollyfield et al were the first to demonstrate a molecular pathway from the initial oxidative damage to tissue molecules, leading to activation of inflammation via the complement system and the development of an antibodymediated immune response, and histopathological changes typical of AMD (Hollyfield et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…4 It is relevant that perinatal inflammation, often caused or exacerbated by oxidative stress, features in the pathogenesis of common diseases of prematurity. [5][6][7] Several investigators have suggested dietary carotenoids might enhance retinal function in infants [8][9][10][11] and protect against inflammation and oxidative damage. [12][13][14][15][16] However, research into this important subject in neonatal nutrition is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[ 104] In another study conducted on 50 subjects affected by dry skin, lutein supplements proved out to be beneficial and resulted in a decrease in 40% of oxidative stress when measured by various vision surveillance tests. [105] Authors have also documented lutein as one of naturally occurring carotenoids with antioxidative, antitumorigenic, antiangiogenic, photoprotective, hepatoprotective, and neuroprotective properties.…”
Section: Skin Healthmentioning
confidence: 99%